PENERAPAN MODEL VCT (VALUE CLARIFICATION TECHNIQUE) DENGAN MENGGUNAKAN MEDIA CERITA DAERAH DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK MENINGKATKAN KARAKTER PESERTA DIDIK - Fitriani, Vety; Sundawa, Dadang (JURNAL PENDIDIKAN ILMU SOSIAL, 2016)
Research is moving on from the issue of th e behavior of learners wich displays the attitude that is not commendable, be less attention and enthusiastic in the learning process so that those conditions concern the researcher to know in depth about the importance of the creation of the character of learners. The approach used is the qualitative approach witj action research methods class. Based on the findings of there search result in the field through instruments of direct observation or interviews that the character formation learners positively impact the learning effectiveness againt PKn teachers can identify the behavior of learners, learns can analyse and disclose his opinion regarding media story area, learners understand the material presented by the teacher in the classroom. The VCT model affect the appearance of religiosity attitudes, honesty, intelligence, toughness, concern, democracy.Keywords: Model VCT, media local story, character.